1999
DOI: 10.1523/jneurosci.19-13-05473.1999
|View full text |Cite
|
Sign up to set email alerts
|

Different Contributions of the Human Amygdala and Ventromedial Prefrontal Cortex to Decision-Making

Abstract: The somatic marker hypothesis proposes that decision-making is a process that depends on emotion. Studies have shown that damage of the ventromedial prefrontal (VMF) cortex precludes the ability to use somatic (emotional) signals that are necessary for guiding decisions in the advantageous direction. However, given the role of the amygdala in emotional processing, we asked whether amygdala damage also would interfere with decision-making. Furthermore, we asked whether there might be a difference between the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

74
1,343
8
46

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,647 publications
(1,483 citation statements)
references
References 35 publications
74
1,343
8
46
Order By: Relevance
“…EDA and HR accelerations during active bet selection were sensitive to the chances of winning. Previous research using the IGT showed that peripheral arousal is sensitive to the reward/punishment contingencies of decision options under ambiguity (e.g., Bechara et al, 1999, 1997; Crone et al, 2004; Tchanturia et al, 2007; Tomb, Hauser, Deldin, & Caramazza, 2002). In contrast, only a handful of prior studies investigated whether such peripheral sensitivities also manifest during decision making under explicit risk, where the reward contingencies are fully described and do not need to be learned through trial and error.…”
Section: Discussionmentioning
confidence: 99%
“…EDA and HR accelerations during active bet selection were sensitive to the chances of winning. Previous research using the IGT showed that peripheral arousal is sensitive to the reward/punishment contingencies of decision options under ambiguity (e.g., Bechara et al, 1999, 1997; Crone et al, 2004; Tchanturia et al, 2007; Tomb, Hauser, Deldin, & Caramazza, 2002). In contrast, only a handful of prior studies investigated whether such peripheral sensitivities also manifest during decision making under explicit risk, where the reward contingencies are fully described and do not need to be learned through trial and error.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the task tests a person's ability to choose between high gains with a risk for even higher losses, and low gains with a risk for smaller losses. Patients with lesions in the VMPFC consistently performed more poorly on this task than controls (Bechara et al, 2000a(Bechara et al, , 1999(Bechara et al, , 1997(Bechara et al, , 1994. Substance abusers also show performance deficits on this task (Bartzokis et al, 2000;Grant et al, 2000).…”
Section: Introductionmentioning
confidence: 91%
“…Substance abusers also show performance deficits on this task (Bartzokis et al, 2000;Grant et al, 2000). Performance on the Iowa Gambling Task appears to be mediated by a neural network composed of the OFC, the amygdala, somatosensory/insular cortices, and the peripheral nervous system (Bechara et al, 1999(Bechara et al, , 1997Ernst et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Decision-making task between high-risk, high-yield choices and low-risk, low-yield choices Impaired performance on gambling task for patients with selective amygdala damage, but not patients with hippocampus damage; skin conductance responses reduced beyond that seen in patients with orbitofrontal damage alone (Bechara et al, 1999;Brand et al, 2007) Feedback loop involving medial prefrontal cortex, comparing current (lateral nucleus of the amygdala) and past (hippocampus) affective valence (Brand et al, 2007;Sotres-Bayon et al, 2004) Emotion facilitation in autism 45 through thalamo-amygdala pathways. Recently, Larson et al (2006) reported brief but strong amygdala responses to pictures of spiders in a functional magnetic resonance imaging (f MRI) study of spider phobic participants, in contrast to weaker but more sustained amygdala activation in healthy comparison participants.…”
Section: Snake In the Grassmentioning
confidence: 97%